Beetles in selected highlands of Marilog District and Lower Tugbok District, Davao City - Gayagas, Angelo A. (2010)
The study provides a glimpse on the current colepteran diversity in the two locations, and may also serve as guide for further ecological studies about coleopterans in highlands and lowlands ecosystem. An inventory of the beetle on selected highlands of Marilog District and lower elevation of Tugbok District, Davao City was conducted to generate baseline information regarding coleopterans species inhabiting in the area. Collection of beetle was done in 3 sampling sites in Marilog District (Datu Salumay, Sitio Epol,and Sitio New Calinan) and 3 sampling sites in Tugbok District (Bagho Oshiro, Manmabulan and Mintal) in the months o October, December and May 2007 and October, December and May 2008. A total of 100 beetle species were cataloged and identified, 98 of which belong to the following 15 families and two unidentified taxa. The families were Attelbidae, Buprestidae, Cantharidae, Carabidae, Cerambycidae, Chrysomelidae, Cicindelidae, Coccinelidae, Cucurlionidae, Elateridae, Lampyridae, Lucanidae, Passalidae, Scarabidae, and Tenebrionidae. The study provides a glimpse on the current coleopteran diversity in the two locations. This study may also serve as guide for further ecological studies about coleopterans in highlands and lowlands ecosystem
Thesis (BS Biology) -- University of the Philippines Mindanao, 2010
Keywords: Baseline information; Coleopterans; Coleopterans -- Marilog District, Davao City; Coleopterans -- Tugbok District, Davao City; Higlands ecosystem; Lowlands ecosystem